2016
DOI: 10.5713/ajas.15.0642
|View full text |Cite
|
Sign up to set email alerts
|

The effect of partial substitution of roasted soybean seed with graded levels of sweet potato (Ipomoea batatas) leaf meal on growth performances and carcass characteristics of broiler chickens

Abstract: This study was designed to assess the effects of partial substitution of roasted soybean seed with sweet potato (Ipomoea batatas) leaf meal (SPLM) on growth performances and carcass components of broiler chickens. The experiment was a completely randomized design consisting of five dietary treatments replicated four times with ten chicks each. The control diet (treatment 1, T1) contained roasted soybean seed as the major protein source without SPLM and treatment diets containing SPLM at the levels of 30 g/kg (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
3
5
0
Order By: Relevance
“…But the lungs and large intestine are nonsignificant ( P > 0.05) among different dietary treatments described in Table 6 . This study agreed with the result of Melesse et al [ 27 ] who observed the broilers who fed on ( T 2 ) (30 g/kg SPLM) had higher slaughter weight and things weight. The current study shows controversy with Mozafari et al's [ 28 ] work who used the different level of cooked and raw potato replacing with 25 and 35% seed of maize which reported that the dietary treatments had nonsignificant effect ( P > 0.05) on weight of thighs, breast, and liver of broiler chicks.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…But the lungs and large intestine are nonsignificant ( P > 0.05) among different dietary treatments described in Table 6 . This study agreed with the result of Melesse et al [ 27 ] who observed the broilers who fed on ( T 2 ) (30 g/kg SPLM) had higher slaughter weight and things weight. The current study shows controversy with Mozafari et al's [ 28 ] work who used the different level of cooked and raw potato replacing with 25 and 35% seed of maize which reported that the dietary treatments had nonsignificant effect ( P > 0.05) on weight of thighs, breast, and liver of broiler chicks.…”
Section: Resultssupporting
confidence: 93%
“…But the lungs and large intestine are nonsignificant (P > 0:05) among different dietary treatments described in Table 6. This study agreed with the result of Melesse et al [27] who observed the broilers who fed on (T 2 ) (30 g/kg SPLM) had higher slaughter weight and things weight. The current study shows controversy with Mozafari et al's [28] work…”
Section: Carcass Componentssupporting
confidence: 93%
“…A healthy diet should contain 1-2% of its calories from fat, according to various theories. This is because the low crude fat content of the young shoot of Urtica simensis shows that it might shield people from chronic diseases [ 25 ]. The leaves of Erucastrum abyssinicum had the least crude fibre content (7.80 ± 0.2 g/100 g), whereas the crude fibre content of Rumex abyssinicus was (34.70 ± 0.25 g/100 g).…”
Section: Resultsmentioning
confidence: 99%
“…The treatment was better compared to control (219.20 (T1), 200.10 (T2), and 215.30 (T3) vs. 243.30 U/L). Melesse et al, (2017) stated the criteria GOT were at the number less than 40 U/L. The result of the GOT may be due to M. oleifera content.…”
Section: Growth Performancementioning
confidence: 97%